Studies of polyethylene-based biocomposites, bionanocomposites and other non-biobased nanocomposites - Sarifuddin, Norshahida; Ismail, Hanafi (Wiley-Scrivener, John Wiley & Sons, Inc., 2016)
Polyethylene is by far the most commonly used commodity thermoplastic. Therefore, this chapter addresses various aspects of polyethylene-based composites. It is intended as a review of recent advances in the development of polyethylene-based composites, particularly biocomposites, bionanocomposites as well as non-biobased nanocomposites. Among various biopolymers, starch is the one most often blended with polyethylene. In a few systems natural fibers have been incorporated into the blend to impart degradation and stabilization of polymers. Due to the excellent attributes of hollow tubular nanostructure, halloysites have a number of exciting applications in the polyethylene-based bionanocomposites. In addition, particular attention is also given to the state of research into carbon nanotubes reinforced polyethylene composites.